The physics of the cosmic microwave background - Guimarães, Luiz Filipe de Oliveira (Cadernos de Astronomia, 2023)
The cosmic microwave background radiation is one of the main observables of cosmology since its discovery. Itallows the investigation of the cosmos from its first moments: from the primordial universe, through the epochof its formation, and to the present time. We can extract, from its statistical properties, traces from all epochsof the universe. In this review, we detail how the background radiation was predicted, detected, and how itsanalysis provides the best descriptions of the past and present universe.
Keywords: cosmology; primordial universe; cosmic microwave background